Learning competencies of pupils before and after the integration of movements - Garcia, Maria Angeles Imelda L. (2014)
Movements stimulate thinking, which is a key to learning. The more senses the children use, the greater is their opportunity to advance their perceptual skills. This study intended to prove such by determining and comparing the levels of competence of the experimental group before and after the integration of prescribed movements in their Language and Reading classes. Levels of competence were measured using their pretest and posttest which were further compared with those of the control group. Selected fifth graders participated in this experiment in SY 2007-2008. The standardized test results during their 4th and 5th grades were compared as the pretest and posttest respectively. The standardized test results in Language and Reading were used to determine the impact of the integration. The findings indicated that indeed the integration of movements has significant effect on the level of competencies of the pupils in most of the areas.
Keywords: Competency, Learning